Looking for a safe haven: tail-anchored proteins and their membrane insertion pathways. Issue 4 (21st June 2021) - Mehlhorn, Dietmar G; Asseck, Lisa Y; Grefen, Christopher
Abstract: Insertion of membrane proteins into the lipid bilayer is a crucial step during their biosynthesis. Eukaryotic cells face many challenges in directing these proteins to their predestined target membrane. The hydrophobic signal peptide or transmembrane domain (TMD) of the nascent protein must be shielded from the aqueous cytosol and its target membrane identified followed by transport and insertion. Components that evolved to deal with each of these challenging steps range from chaperones to receptors, insertases, and sophisticated translocation complexes. One prominent translocation pathway for most proteins is the signal recognition particle (SRP)-dependent pathway which mediates co-translational translocation of proteins across or into the endoplasmic reticulum (ER) membrane. This textbook example of protein insertion is stretched to its limits when faced with secretory or membrane proteins that lack an amino-terminal signal sequence or TMD. Particularly, a large group of so-called tail-anchored (TA) proteins that harbor a single carboxy-terminal TMD require an alternative, post-translational insertion route into the ER membrane. In this review, we summarize the current research in TA protein insertion with a special focus on plants, address challenges, and highlight future research avenues. Abstract : Update on different pathways and candidates that facilitate membrane insertion of tail-anchored proteins in eukaryotes with a special emphasis on recent insights in plant research.